TINJAUAN FAKTOR PENYEBAB DUPLIKASI PENOMORAN REKAM MEDIS DI RS PANTI WALUYO SURAKARTA: TINJAUAN FAKTOR PENYEBAB DUPLIKASI PENOMORAN REKAM MEDIS DI RS PANTI WALUYO SURAKARTA - Saryadi Saryadi; Ambar Setiti; Liss Dyah Dewi Arini (Jurnal Keperawatan Duta Medika, 2023)
Introduction: The numbering system at Panti Waluyo Hospital Surakarta is a Unit Numbering System where one patient gets one medical record number. In 2021, there were 94 duplicate medical record documents. Objectives: This study aims to determine the factors that cause duplication of medical record numbering at Panti Waluyo Hospital, Surakarta.Methods: The type of research used is descriptive research with a cross sectional approach to data collection by observation and interviews, purposive sampling, research instruments using interview guidelines and observation guidelines, data processing using collecting, editing, and presenting data in a description.Results: the factors that cause duplication of medical record numbering are the man factor due to the inaccuracy of the officer, the material factor because the patient does not bring the KIB, the machine factor because the patient card printing machine is having trouble and the method factor already has a patient numbering SPO and patient registration flow. The impact on the patient's medical history is unsustainable, uneconomical, and the filing shelves fill up quickly. To minimize duplication, the efforts made are guided by SOPs, patient education to bring KIB, maintenance of patient card printing machines, adding data search items on SIMRS and merging medical record numbers.Conclusions: Factors causing duplication of medical record numbering at Panti Waluyo Hospital are caused by man, material, machine and method factors. The author suggests that registration officers should communicate with patients, check patient data and immediately merge medical record numbers in case of duplication.